Optimalisasi Performa Sistem Operasi melalui Integrasi Arsitektur Heterogen dan Virtualisasi di Era Komputasi Awan - Muhammad Rinov Cuhanazriansyah; Shelomita Putri Agustina; Sigit Gilang Pamungkas Raharjo; Achmad Sultoni Ichwana (Universitas Sains Indonesia Publishing, 2025)
As cloud computing continues to grow, more stable and efficient operating systems are required to manage increasingly complex workloads. To improve system performance and flexibility, the integration of virtualization technology and heterogeneous architectures such as CPUs, GPUs, and FPGAs is essential. To determine how effective the applied optimization techniques and architectures are, this study employs qualitative and quantitative methods using literature analysis, interviews, and surveys. The findings indicate that dynamic virtual machine consolidation and memory optimization can enhance data center resource utilization and reduce latency by up to 25%. Technologies such as edge and fog computing also improve response speed and service availability. Overall, the combination of virtualization and heterogeneous architectures serves as an effective strategy for maximizing operating system performance in cloud computing environments.